Pengalaman Orang Tua dalam Memberikan MPASI Abon Monas Prest pada Baduta di Desa Kelir Banyuwangi - Vina Aprilia Lestari; Badrul Munif; Yulifah Salistia Budi (Pusat Riset dan Inovasi Nasional, 2024)
Inappropriate complementary food given by parents to children under two years old is one of the causes of nutritional problems in children. There are still many parents who have insufficient knowledge about complementary foods and do not know the important ingredients that must be in them. The aim of this research is to explore various experiences of parents in providing MPASI Shredded Monas Perst to toddlers. Therefore, the solution to overcome this problem is to provide the right complementary food, namely Abon Monas Prest with a high content of protein and other micronutrients at a more affordable price. This study used qualitative with phenomenology approach. The population was 12 participants selected using purposive sampling technique, and obtained sample as many as 9 participants. The data analysis used Miles and Huberman model. The themes obtained were, 1) Parents feeling when giving complementary food, Abon Monas Prest for the first time, 2) Increased appetite in children under two years of age, 3) Supportive response from family members in providing complementary food, Abon Monas Prest. Giving complementary food, Abon Monas Prest can give parental knowledge​ about giving the right complementary food for overcome nutritional problems​ with increase lust feeding to children age under two year. Besides that, support member family is also important given to Mother child in giving right complementary food.